Compare Comparison of Sustainability Performance, Financial Performance, and Company Values Before and During the COVID-19 Pandemic in Mining Sector Companies - Edra Arkananda Gultom; Kurnia Ekasari; Hesti Wahyuni (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to find out and compare whether or not there are differences between sustainability performance, financial performance, and company value before and during the COVID-19 Pandemic. This research examines mining sector companies listed on the Indonesia Stock Exchange in 2018-2021. Sampling was carried out using the purposive sampling method and obtained from five companies. The data used in this research is secondary data. The sustainability performance variable is obtained from the SRDI calculation results, the financial performance variable is obtained using Return on Assets (ROA), and the company value variable is obtained using the Price Earning Ratio (PER). The normality test in this study used the One-Sample Kolmogorov Smirnov Test method and it was concluded that the SRDI data were normally distributed so the Independent Sample T-Test was used, while the ROA and PER data were not normally distributed so the Mann Whitney Test nonparametric different test was used. The results of the study found that there were no significant differences in the variables: sustainability performance (SRDI), financial performance (ROA), and company value Price (PER) before and during the COVID19 Pandemic.